Team Cohesion: A Theoretical Consideration of Its Reciprocal Relationships within the Team Adaptation Nomological Network - Maynard, M.; Kennedy, D. M.; Sommer, S. A.; Passos, A. M. (Research on Managing Groups and Teams, 2015)
While the topic of team adaptation is gaining in prominence within the broader team effectiveness literature, there remain numerous unanswered questions about the way it affects, and is affected by, team dynamics over time. In particular, within this chapter, we seek to more fully examine the relationship between team adaptation and team cohesion to set the stage for additional investigations of team adaptation – team emergent state relationships. However, beyond merely suggesting that a linear relationship exists between team adaptation and cohesion, we envision the relationship as likely being curvilinear as well as reciprocal in nature. Additionally, we consider how temporal factors may shape this relationship by considering how the team’s performance on prior disruptions may influence the link between team cohesion and different adaptive outcomes (i.e., meritorious, maintenance, or maladaptation) as well as flowing along a feedback loop to affect team adaptation processes and team adaptability. By theorizing about these underexamined relationships, our intent is to introduce a framework that can be utilized as a foundation upon which future team adaptation research can build. Finally, we discuss how practitioners can leverage our thoughts in order to more effectively manage adaptation and cohesion within their teams.